"Therapeutic applications of the 'NPGP' family of viral 2As". (9th August 2018) - Luke, Garry A.; Ryan, Martin D.
Summary: Oligopeptide "2A" and "2A‐like" sequences ("2As"; 18‐25aa) are found in a range of RNA virus genomes controlling protein biogenesis through "recoding" of the host‐cell translational apparatus. Insertion of multiple 2As within a single open reading frame (ORF) produces multiple proteins; hence, 2As have been used in a very wide range of biotechnological and biomedical applications. During translation, these 2A peptide sequences mediate a eukaryote‐specific, self‐"cleaving" event, termed "ribosome skipping" with very high efficiency. A particular advantage of using 2As is the ability to simultaneously translate a number of proteins at an equal level in all eukaryotic systems although, naturally, final steady‐state levels depend upon other factors—notably protein stability. By contrast, the use of internal ribosome entry site elements for co‐expression results in an unbalanced expression due to the relative inefficiency of internal initiation. For example, a 1:1 ratio is of particular importance for the biosynthesis of the heavy‐chain and light‐chain components of antibodies: highly valuable as therapeutic proteins. Furthermore, each component of these "artificial polyprotein" systems can be independently targeted to different sub‐cellular sites. The potential of this system was vividly demonstrated by concatenating multiple gene sequences, linked via 2A sequences, into a single, long, ORF—a polycistronic construct. Here, ORFs comprising the biosynthetic pathways for violacein (five gene sequences) and β‐carotene (four gene sequences) were concatenated into a single cistron such that all components were co‐expressed in the yeast Pichia pastoris . In this review, we provide useful information on 2As to serve as a guide for future utilities of this co‐expression technology in basic research, biotechnology, and clinical applications.